CURABLE COMPOSITION, CURED FILM, ORGANIC EL DEVICE, AND METHOD FOR PRODUCTION THEREOF

By using a combination of absorbable agents of cycloalkyl formate-derived macrocycloallyl derivatives, multifunctional allylene derivatives and monofunctional oxyethylene derivatives, a package layer with low dielectric constant and high glass transition temperature is formed, which solves the problem of deformation and cracking of the packaging layer at high temperatures in the prior art, and reduces the dielectric constant in the touch screen system, avoiding functional failure.

JP7662758B1Active Publication Date: 2025-04-15JSR CORPORATION
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023214892
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-11-15
Filing Date
2023-12-20
Publication Date
2025-04-15
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

The packaging structure of existing organic electroluminescent (organic EL) devices is prone to deformation and cracking at high temperatures, and in touch screen systems, the high dielectric constant of the packaging layer will cause functional failure.

Method used

Using a combination of absorbable agents with an absorbable agent content of more than 85%, including a absorbable agent system composed of macrocycloallyl derivatives derived from cycloalkyl formate, multifunctional allylene derivatives and monofunctional oxyethylene derivatives, an encapsulation layer with low dielectric constant and high glass transition temperature is formed by photocuring.

Benefits of technology

It is realized that the dielectric constant of the packaging layer is reduced without increasing the glass transition temperature, and the functional failure caused by the high dielectric constant is avoided, and the mechanical strength and waterproof performance of the packaging layer are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662758000001
    Figure 0007662758000001
  • Figure 0007662758000002
    Figure 0007662758000002
  • Figure 0007662758000003
    Figure 0007662758000003
Patent Text Reader

Abstract

The present invention provides a curable composition capable of forming a cured product having a low dielectric constant and a sufficiently high glass transition temperature. The present invention provides a curable composition containing a polymerizable compound and a polymerization initiator, the polymerizable compound being represented by the formula (1): R 1 -X 1 -R 2 (In formula (1), R 1 and R 2 are each independently a substituted or unsubstituted alicyclic oxiranyl group. 1 is a divalent hydrocarbon group or a halogenated hydrocarbon group.), a polyfunctional polymerizable compound (A2) (excluding compound (A1)), and a monofunctional polymerizable compound (A3) having one oxetanyl group in one molecule, wherein the total amount of compound (A1), compound (A2) and compound (A3) is 85 mass% or more based on the total amount of the polymerizable compounds.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition, a cured film, an organic EL device, and a method for producing the same. [Background technology]

[0002] An organic electroluminescence element (organic EL element) is a light-emitting element having a laminated structure including an anode, an organic light-emitting layer, and a cathode. Organic EL elements are widely used in various applications such as display devices and lighting devices.

[0003] The organic light-emitting layer of an organic EL element is easily deteriorated by contact with moisture and oxygen, and there is a concern that, for example, moisture that has penetrated into the element over a long period of operation may cause partial non-emitting areas (hereinafter also referred to as "dark spots") to form, and that light-emitting characteristics may deteriorate due to contact with moisture and oxygen. Therefore, conventionally, organic EL elements are provided with a sealing structure that seals the organic light-emitting layer, and the sealing structure prevents the organic light-emitting layer from coming into contact with moisture and oxygen (for example, see Patent Documents 1 to 4).

[0004] Patent Document 1 discloses that a sealing structure for covering an organic light-emitting layer is formed using a curable composition containing a polymerizable compound having two or three vinyl groups bonded to a naphthalene ring and a polymerization initiator.

[0005] Patent Document 2 discloses a sealant for an organic EL display element, which contains, as the cationic polymerizable compound in a curable composition containing a cationic polymerizable compound and a cationic polymerization initiator, a cycloalkene oxide-type alicyclic epoxy compound and a compound having a biphenyl skeleton and an epoxy group or an oxetanyl group.

[0006] Patent Documents 3 and 4 disclose that a sealing structure for an organic EL element is formed by curing a sealant composition containing an alicyclic epoxy compound, a monofunctional or polyfunctional oxetane compound, and an aliphatic epoxy compound as polymerizable compounds. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2020-26515 A [Patent Document 2] International Publication No. 2021 / 010226 [Patent Document 3] Korean Patent Publication No. 10-2022-0160362 [Patent Document 3] Korean Patent Publication No. 10-2023-0032669 Summary of the Invention [Problem to be solved by the invention]

[0008] A laminate of inorganic sealing layer / organic sealing layer / inorganic sealing layer is generally used for the sealing structure of an organic EL element. When forming such a laminate, an inorganic sealing layer (e.g., a nitride film), an organic sealing layer, and an inorganic sealing layer are laminated in this order. In such a case, if the glass transition temperature (Tg) of the organic sealing layer is low, there is a concern that the organic sealing layer may be distorted when the inorganic sealing layer is formed on the organic sealing layer, which may cause cracks.

[0009] In addition, in an organic EL light-emitting device that employs a touch panel system, a touch sensor is disposed on the substrate. In the case of a touch panel system, if the dielectric constant of the sealing structure (particularly the organic sealing layer) is high, there is a concern that the touch panel may malfunction when in use. Therefore, it is desirable for the organic sealing layer of the sealing structure to have a low dielectric constant, but there is a trade-off between lowering the dielectric constant and increasing the Tg of the cured film, and attempting to lower the dielectric constant of the cured film results in a high Tg.

[0010] The present invention has been made in consideration of the above problems, and has as its main object to provide a curable composition capable of forming a cured product having a low dielectric constant and a sufficiently high glass transition temperature. [Means for solving the problem]

[0011] According to the present invention, there are provided the following curable composition, cured film, organic EL device and production method thereof, and compound.

[0012] [1] A curable composition containing a polymerizable compound and a polymerization initiator, wherein the polymerizable compound is represented by the following formula (1): R 1 -X 1 -R 2 …(1) (In formula (1), R 1 and R 2 are each independently a substituted or unsubstituted alicyclic oxiranyl group. 1 is a divalent hydrocarbon group or a halogenated hydrocarbon group. a compound (A2) which is a polyfunctional polymerizable compound (excluding the compound (A1)), and a compound (A3) which is a monofunctional polymerizable compound having one oxetanyl group in one molecule, wherein the total amount of the compound (A1), the compound (A2) and the compound (A3) is 85 mass% or more based on the total amount of the polymerizable compounds. [2] A curable composition containing a polymerizable compound and a polymerization initiator, the polymerizable compound containing a compound represented by the above formula (1), a polyfunctional polymerizable compound (excluding the above compound (A1)), and a monofunctional polymerizable compound, wherein a cured product of the curable composition has a dielectric constant of 2.70 or less at 25°C and a frequency of 250 kHz, and a glass transition temperature of 85°C or more. [3] A cured film formed using the curable composition according to [1] or [2] above. [4] An organic EL element comprising an organic light-emitting layer and an organic sealing layer that seals the organic light-emitting layer, wherein the organic sealing layer is formed using the curable composition according to [1] or [2] above. [5] A method for producing an organic EL element including an organic light-emitting layer and an organic sealing layer sealing the organic light-emitting layer, the method comprising the steps of: applying the curable composition according to [1] or [2] above to a light-emitting layer-forming surface of a substrate on which the organic light-emitting layer is formed; and forming the organic sealing layer by irradiating radiation to cure the curable composition. Effect of the Invention

[0013] According to the curable composition of the present invention, it is possible to obtain a cured product having a low dielectric constant and a sufficiently high glass transition temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Matters related to the embodiments will be described in detail below. In this specification, a numerical range described using "to" means that the numerical range includes the numerical ranges before and after "to" as the lower and upper limits.

[0015] In this specification, the term "hydrocarbon group" includes chain-shaped hydrocarbon groups, alicyclic hydrocarbon groups, and aromatic hydrocarbon groups. The term "chain-shaped hydrocarbon group" refers to a straight-chain hydrocarbon group and a branched hydrocarbon group that do not include a cyclic structure in the main chain and are composed only of a chain structure. However, the chain-shaped hydrocarbon group may be saturated or unsaturated. The term "alicyclic hydrocarbon group" refers to a hydrocarbon group that includes only an alicyclic hydrocarbon structure as a ring structure and does not include an aromatic ring structure. However, the alicyclic hydrocarbon group does not need to be composed only of an alicyclic hydrocarbon structure, and also includes those that have a chain structure as a part of it. The term "aromatic hydrocarbon group" refers to a hydrocarbon group that includes an aromatic ring structure as a ring structure. However, the aromatic hydrocarbon group does not need to be composed only of an aromatic ring structure, and may include a chain structure or an alicyclic hydrocarbon structure as a part of it. The ring structures of the alicyclic hydrocarbon group and the aromatic hydrocarbon group may have a substituent group consisting of a hydrocarbon structure.

[0016] 《Curable composition》 The curable composition of the present disclosure (hereinafter also referred to as "the composition") contains a polymerizable compound and a polymerization initiator. The composition of the first embodiment of the composition (hereinafter also referred to as "the first composition") contains the following compounds (A1), (A2) and (A3) as polymerizable compounds. Compound (A1): A compound represented by the following formula (1): R 1 -X 1 -R 2 …(1) (In formula (1), R 1 and R 2 are each independently a substituted or unsubstituted alicyclic oxiranyl group. 1 is a divalent hydrocarbon group or a halogenated hydrocarbon group. Compound (A2): A polyfunctional polymerizable compound (excluding compound (A1)). Compound (A3): A monofunctional polymerizable compound having one oxetanyl group in one molecule.

[0017] Each component contained in the first composition and other components that are blended as necessary are described below. Unless otherwise specified, each component may be used alone or in combination of two or more.

[0018] <Polymerizable compound> A polymerizable compound is a general term for a compound that hardens when exposed to radiation or heat. A polymerizable compound has one or more functional groups (hereinafter also referred to as "polymerizable functional groups") that polymerize when exposed to radiation or heat in one molecule.

[0019] As the polymerizable compound, a compound having one or more functional groups having cationic polymerizability (hereinafter also referred to as "cationically polymerizable group") as a polymerizable functional group can be preferably used. Examples of the cationic polymerizable group include an oxetanyl group, an oxiranyl group, and a vinyl ether group. From the viewpoint of polymerization, a compound having an oxetanyl group or an oxiranyl group can be preferably used as the polymerizable compound.

[0020] The molecular weight of the polymerizable compound is, for example, 50 to 800, preferably 70 to 600, and more preferably 100 to 500, in that the viscosity can be easily adjusted to a value suitable for inkjet coating.

[0021] The first composition contains, as polymerizable compounds, a monofunctional compound having one polymerizable functional group in one molecule and a polyfunctional compound having two or more polymerizable functional groups in one molecule. Among the polymerizable compounds contained in the first composition, the compound (A1) and the compound (A2) are polyfunctional polymerizable compounds, and the compound (A3) is a monofunctional polymerizable compound. Hereinafter, the compounds (A1) to (A3) will be described respectively.

[0022] ·Compound (A1) The compound (A1) is a compound represented by the above formula (1). In the above formula (1), R 1 or R 2 A preferred specific example of the substituted or unsubstituted alicyclic oxiranyl group represented by the following formula (1a) is mentioned. [ka] (In formula (1a), R 7 is an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 20 carbon atoms. n is an integer of 0 to 3. "*" represents a bond.

[0023] In the above formula (1a), R 7 The alkyl group having 1 to 6 carbon atoms represented by the formula (I) may be linear or branched. 7 Examples of the aryl group having 6 to 20 carbon atoms represented by the formula (I) include a phenyl group, a methylphenyl group, an ethylphenyl group, a dimethylphenyl group, and a diethylphenyl group. R 7 Of these, an alkyl group having 1 to 3 carbon atoms or a phenyl group is preferable. n is preferably 0 to 2, more preferably 0 or 1, and further preferably 0.

[0024] From the viewpoint of reactivity to radiation or heat, R 1and R 2 Among the above, each of is preferably a substituted or unsubstituted 3,4-epoxycyclohexyl group, and more preferably a 3,4-epoxycyclohexyl group.

[0025] In the above formula (1), X 1 Examples of the divalent hydrocarbon group represented by the formula (I) include a divalent chain hydrocarbon group, a divalent alicyclic hydrocarbon group, and a divalent aromatic hydrocarbon group. Specific examples of the divalent chain hydrocarbon group include a linear or branched divalent saturated hydrocarbon group having 1 to 20 carbon atoms, and a linear or branched divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms. Of these, X 1 The divalent chain hydrocarbon group represented by the following formula is preferably a linear or branched divalent saturated hydrocarbon group having 1 to 20 carbon atoms.

[0026] Examples of the divalent alicyclic hydrocarbon group include groups in which two hydrogen atoms have been removed from the ring or chain portion of an alicyclic hydrocarbon having a saturated or unsaturated aliphatic ring having 3 to 20 carbon atoms. Specific examples of the ring contained in the divalent alicyclic hydrocarbon group include monocyclic saturated alicyclic hydrocarbons such as a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, and a cyclooctane ring; monocyclic saturated alicyclic hydrocarbons such as a cyclobutene ring, a cyclopentene ring, a cyclohexene ring, a cycloheptene ring, and a cyclooctene ring; polycyclic saturated alicyclic hydrocarbons such as a decahydronaphthalene ring, an octahydronaphthalene ring, a norbornane ring, and a bicyclo[2.2.2]octane ring; and polycyclic saturated alicyclic hydrocarbons such as a norbornene ring, a tetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene and other polycyclic unsaturated alicyclic hydrocarbons; and the like.

[0027] Divalent aromatic hydrocarbon groups include groups in which two hydrogen atoms have been removed from a ring or chain portion of an aromatic hydrocarbon having a single ring or condensed ring (for example, a benzene ring, a naphthalene ring, an anthracene ring).

[0028] X 1Examples of the divalent halogenated hydrocarbon group represented by the formula (1) include the above-mentioned divalent hydrocarbon group in which one or more hydrogen atoms are substituted with halogen atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0029] The first composition is advantageous in that it can lower the dielectric constant of the cured product obtained by the first composition while increasing the Tg of the cured product. 1 is preferably a divalent group represented by the following formula (1b). *-C(R 3 )(R 4 )-* …(1b) (In formula (1b), R 3 and R 4 are each independently a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a fluoroalkyl group having 1 to 3 carbon atoms, or a phenyl group, or R 3 and R 4 are combined together and R 3 and R 4 represents an alicyclic structure formed together with the carbon atom to which it is bonded. "*" represents a bond to the alicyclic oxirane ring structure.)

[0030] In the above formula (1b), R 3 or R 4 The alkyl group and fluoroalkyl group having 1 to 3 carbon atoms represented by the following formula may be linear or branched. R 3 and R 4 are combined together and R 3 and R 4 Examples of the alicyclic structure formed together with the carbon atom to which is bonded include a cyclopentane ring structure, a cyclohexane ring structure, and a cycloheptane ring structure. The alicyclic structure may have a substituent in the ring portion. Examples of the substituent include an alkyl group having 1 to 3 carbon atoms and a halogen atom.

[0031] The first composition has a higher effect of lowering the dielectric constant and increasing the Tg of the cured product, which is advantageous in that 3 and R 4are each a hydrogen atom, a methyl group, an ethyl group, a trifluoromethyl group, or a phenyl group, or R 3 and R 4 are combined together and R 3 and R 4 is preferably an alkyl-substituted or unsubstituted cyclohexane-1,1-diyl group formed together with the carbon atom to which R is bonded, more preferably a hydrogen atom, a methyl group, an ethyl group, or a trifluoromethyl group, 3 and R 4 More preferably, both are methyl groups.

[0032] A preferred specific example of the compound (A1) is a compound represented by the following formula (1-1). [ka] (In formula (1-1), R 3 and R 4 are each independently a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a fluoroalkyl group having 1 to 3 carbon atoms, or a phenyl group, or R 3 and R 4 are combined together and R 3 and R 4 R represents an alicyclic structure formed together with the carbon atom to which it is bonded. 5 and R 6 are each independently an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 20 carbon atoms. n1 and n2 are each independently an integer of 0 to 3.

[0033] In the above formula (1-1), R 3 and R 4 Specific and preferred examples of R 3 and R 4 is the same as: R 5 and R 6 Specific and preferred examples of R 7 The groups are the same as those exemplified in the explanation of the above. Each of n1 and n2 is preferably 0 to 2, more preferably 0 or 1, and further preferably 0.

[0034] Further specific examples of the compound (A1) include bis(3,4-epoxycyclohexyl)methane, 1,1-bis(3,4-epoxycyclohexyl)ethane, 1,2-bis(3,4-epoxycyclohexyl)ethane, 2,2-bis(3,4-epoxycyclohexyl)propane, 2,2-bis(3,4-epoxycyclohexyl)hexafluoropropane, 2,2-bis(3,4-epoxycyclohexyl)butane, 1,1-bis(3,4-epoxycyclohexyl)cyclohexane, and 1,1-bis(3,4-epoxycyclohexyl)-3,3,5-trimethylcyclohexane.

[0035] Among the above, the compound (A1) is selected from the group consisting of bis(3,4-epoxycyclohexyl)methane, 1,1-bis(3,4-epoxycyclohexyl)ethane, 1,2-bis(3,4-epoxycyclohexyl)ethane, 2,2-bis(3,4-epoxycyclohexyl)propane, 2,2-bis(3,4-epoxycyclohexyl)hexafluoropropane, and 2,2-bis(3,4-epoxycyclohexyl)butane. At least one selected from the group consisting of 1,1-bis(3,4-epoxycyclohexyl)ethane, 2,2-bis(3,4-epoxycyclohexyl)propane, 2,2-bis(3,4-epoxycyclohexyl)hexafluoropropane, and 2,2-bis(3,4-epoxycyclohexyl)butane is preferred, and 2,2-bis(3,4-epoxycyclohexyl)propane is particularly preferred.

[0036] In the present composition, the content of the compound (A1) is preferably 10 to 60 mass% based on the total amount of the polymerizable compounds contained in the present composition. When the content of the compound (A1) is within the above range, the effect of achieving both low dielectric constant and high Tg of the cured product obtained using the present composition can be sufficiently improved. From the viewpoint of obtaining a sufficient improvement effect of low dielectric constant and high Tg of the cured product, the content of the compound (A1) is more preferably 15 mass% or more based on the total amount of the polymerizable compounds, more preferably 20 mass% or more, and even more preferably 30 mass% or more. In addition, from the viewpoint of improving the curability by blending a compound different from the compound (A1) as a polymerizable compound, the content of the compound (A1) is more preferably 55 mass% or less based on the total amount of the polymerizable compounds.

[0037] ·Compound (A2) The compound (A2) is blended in the first composition to further improve the curability of the curable composition. The compound (A2) is a polyfunctional polymerizable compound, and may be any compound not included in the above formula (1). Examples of the compound (A2) include polyfunctional oxirane compounds (excluding the compound (A1)), polyfunctional oxetane compounds, and polyfunctional vinyl ether compounds.

[0038] Examples of the polyfunctional oxirane compound include a compound having two or more glycidyl groups per molecule (hereinafter also referred to as "polyfunctional glycidyl compound (a2)") and a compound having two or more substituted or unsubstituted alicyclic oxiranyl groups per molecule that is not included in the above formula (1) (hereinafter also referred to as "polyfunctional alicyclic oxirane compound (a2)").

[0039] Among the polyfunctional oxirane compounds, specific examples of the polyfunctional glycidyl compound (a2) include siloxane compounds having two or more glycidyl groups in the molecule, such as the product name "X-40-2728" (both manufactured by Shin-Etsu Chemical Co., Ltd.); Epoxy group-containing resins such as bisphenol A type epoxy resins, bisphenol E type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol O type epoxy resins, 2,2'-diallyl bisphenol A type epoxy resins, hydrogenated bisphenol type epoxy resins, propylene oxide-added bisphenol A type epoxy resins, resorcinol type epoxy resins, biphenyl type epoxy resins, sulfide type epoxy resins, diphenyl ether type epoxy resins, dicyclopentadiene type epoxy resins, naphthalene type epoxy resins, phenol novolac type epoxy resins, ortho-cresol novolac type epoxy resins, dicyclopentadiene novolac type epoxy resins, biphenyl novolac type epoxy resins, naphthalene phenol novolac type epoxy resins, glycidyl amine type epoxy resins, alkyl polyol type epoxy resins, rubber-modified epoxy resins, glycidyl ester compounds, and bisphenol A type episulfide resins.

[0040] Specific examples of the polyfunctional alicyclic oxirane compound (a2) include 3,4-epoxycyclohexylmethyl 3',4'-epoxycyclohexane carboxylate, bis(3,4-epoxycyclohexylmethyl)adipate, bis(3,4-epoxy-6-methylcyclohexylmethyl)adipate, etc. In addition, examples of commercially available products include Celoxide 2021P and Celoxide 8010 (both manufactured by Daicel Corporation); KR-470, X-40-2669, X-40-2670, and X-40-2678 (both manufactured by Shin-Etsu Chemical Co., Ltd.).

[0041] The polyfunctional oxetane compound may be any compound having two or more oxetane rings per molecule. Specific examples of polyfunctional oxetane compounds include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, bis[1-ethyl(3-oxetanyl)]methyl ether, bis(3-ethyl-3-oxetanylmethyl)ether, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,3-bis(3-ethyl-3-oxetanylmethoxy)propane, and 1,4-bis(3-ethyl-3-oxetanylmethoxy). butane, 1,4-bis(3-ethyl-3-oxetanylmethoxymethyl)benzene, 1,3-bis(3-ethyl-3-oxetanylmethoxymethyl)benzene, 1,2-bis(3-ethyl-3-oxetanylmethoxymethyl)benzene, 4,4'-bis(3-ethyl-3-oxetanylmethoxymethyl)biphenyl, 2,2'-bis(3-ethyl-3-oxetanylmethoxymethyl)biphenyl, 1,6-bis((3-methyloxetan-3-yl)methoxy)hexane, 1,6-bis((3-ethyloxetan-3-yl)methoxy)hexane, hydrolysis condensate of 3-[(3-ethyloxetan-3-yl)methoxy]propyltrialkoxysilane, condensation reaction product of 3-ethyloxetan-3-ylmethanol and silanetetraol polycondensate, and compounds represented by the following formulas (2a-1) to (2a-3), respectively. [ka]

[0042] The polyfunctional vinyl ether compound may be any compound having two or more vinyl ether groups per molecule.Specific examples of the polyfunctional vinyl ether compound include compounds having a plurality of vinyl ether groups, such as alkanediol divinyl ether, cycloalkanediol divinyl ether, cycloalkane dimethanol divinyl ether, (poly)ethylene glycol divinyl ether, trimethylolpropane divinyl ether, pentaerythritol divinyl ether, trimethylolpropane trivinyl ether, pentaerythritol trivinyl ether, pentaerythritol tetravinyl ether, and dipentaerythritol hexavinyl ether, and alkylene oxide-modified or caprolactone-modified compounds thereof.

[0043] The compound (A2) preferably has 2 to 10 polymerizable functional groups in one molecule, more preferably 2 to 6 polymerizable functional groups, and even more preferably 2 to 4 polymerizable functional groups in one molecule. The molecular weight of the polymerizable compound is preferably from 50 to 800, more preferably from 70 to 600, and even more preferably from 100 to 500, in that the viscosity can be easily adjusted to a level suitable for inkjet coating.

[0044] In terms of being able to obtain a curable composition exhibiting excellent curability while achieving a low dielectric constant of the cured product, the compound (A2) is preferably at least one selected from the group consisting of a compound having a total of two or more oxetane rings in the molecule (i.e., a polyfunctional oxetane compound) and a polyfunctional alicyclic oxirane compound (a2), and more preferably contains a polyfunctional oxetane compound. The proportion of the polyfunctional oxetane compound is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 65% ​​by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the total amount of the compound (A2) contained in the composition.

[0045] The content of the compound (A2) is preferably 5 to 70 mass% based on the total amount of the polymerizable compounds contained in the composition, from the viewpoint of obtaining a curable composition having excellent curability while reducing the dielectric constant of the cured product. From the viewpoint of improving the curability of the curable composition, the content of the compound (A2) is more preferably 10 mass% or more, and even more preferably 20 mass% or more, based on the total amount of the polymerizable compounds contained in the composition. Moreover, from the viewpoint of increasing the Tg of the cured product, the content of the compound (A2) is more preferably 67 mass% or less, and even more preferably 65 mass% or less, based on the total amount of the polymerizable compounds contained in the composition.

[0046] From the viewpoint of realizing a good balance between a high Tg and a low dielectric constant of the cured film, it is preferable that the content of the compound (A1) is 20% by mass or more based on the total amount of the polymerizable compounds, or the total amount of the compound (A1) and the compound (A2) is 60% by mass or more based on the total amount of the polymerizable compounds. From the viewpoint of achieving a higher Tg and a lower dielectric constant of the cured film, it is more preferable that the content of the compound (A1) is 30% by mass or more based on the total amount of the polymerizable compounds, or the total amount of the compound (A1) and the compound (A2) is 70% by mass or more based on the total amount of the polymerizable compounds.

[0047] ·Compound (A3) Compound (A3) is a monofunctional polymerizable compound having one oxetanyl group in one molecule (i.e., a monofunctional oxetane compound). The monofunctional compound (A3) can be blended into the first composition to improve the wettability and spreadability of the curable composition. In addition, since compound (A3) has an oxetanyl group as a polymerizable functional group, it is less likely to remain as an unreacted polymerizable compound in the cured product, and this can reduce outgassing from the cured product.

[0048] The monofunctional oxetane compound may be any compound having one oxetane ring per molecule. Specific examples of the monofunctional oxetane compound include, for example, 3-ethyl-3-((2-ethylhexyloxy)methyl)oxetane, phenoxymethyloxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-((3-(triethoxysilyl)propoxy)methyl)oxetane, 3-allyloxyoxetane, 3-ethyl-3-allyloxyoxetane, 3-ethyl-3-acryloyloxymethyloxetane, 3-ethyl-3-methacryloxymethyloxetane, and the like. oxetane, 2-methyl-2-allyl-4-propyloxetane, 3-ethyl-3-(4-acryloyloxybutyloxymethyl)oxetane, 3-ethyl-3-(3-acryloyloxy-2,2-dimethylpropyloxymethyl)oxetane, 3-methyl-3-methoxyoxetane, phenyloxetane, 3-ethyl-3-chloromethyloxetane, 3-ethyl-3-oxetanemethanol, 3-amino-3-dimethyloxetane, and the compounds represented by the following formulas (3a-1) to (3a-21). [ka]

[0049] The content of the compound (A3) is preferably 20 to 70 mass% based on the total amount of the polymerizable compounds contained in the composition, from the viewpoint of suppressing the viscosity of the curable composition from becoming too high while lowering the dielectric constant of the cured product and improving the wettability and spreadability of the curable composition. From the viewpoint of improving the wettability and spreadability of the curable composition, the content of the compound (A3) is more preferably 30 mass% or more, and even more preferably 35 mass% or more, based on the total amount of the polymerizable compounds contained in the composition. In addition, the content of the compound (A3) is more preferably 60 mass% or less, and even more preferably 50 mass% or less, based on the total amount of the polymerizable compounds contained in the composition, from the viewpoint of obtaining a cured product having sufficiently high mechanical strength and a low dielectric constant.

[0050] The total amount of the compound (A1), the compound (A2), and the compound (A3) in the first composition is 85% by mass or more based on the total amount of the polymerizable compounds contained in the first composition. If the total amount of the compound (A1), the compound (A2), and the compound (A3) is less than 85% by mass based on the total amount of the polymerizable compounds contained in the first composition, the composition tends not to maintain a balance between a low dielectric constant and a high glass transition temperature Tg of the cured product obtained. In addition, the amount of outgassing from the cured product tends to increase. From the viewpoint of obtaining a cured product that has a low dielectric constant, a sufficiently high glass transition temperature, and little outgassing, the total amount of the compound (A1), the compound (A2), and the compound (A3) in the first composition is more preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more based on the total amount of the polymerizable compounds contained in the first composition.

[0051] Other polymerizable compounds The first composition may contain only the compound (A1), the compound (A2) and the compound (A3) as the polymerizable compound. In addition, for the purpose of adjusting the curability and viscosity of the composition, the first composition may further contain a compound different from the compound (A1), the compound (A2) and the compound (A3) (hereinafter, also referred to as "other polymerizable compound") in addition to the compound (A1), the compound (A2) and the compound (A3). Examples of the other polymerizable compound include a monofunctional oxirane compound and a monofunctional vinyl ether compound.

[0052] Specific examples of other polymerizable compounds include monofunctional oxirane compounds such as cyclohexene oxide, 1-methyl-1,2-epoxycyclohexane, 1,2-epoxy-4-vinylcyclohexane, ethyl glycidyl ether, butyl glycidyl ether, and 1,2-epoxytetradecane. Specific examples of the monofunctional vinyl ether compound include cyclohexyl vinyl ether, ethylhexyl vinyl ether, and hydroxyethyl vinyl ether.

[0053] The content of the other polymerizable compounds is 15% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 2% by mass or less, based on the total amount of polymerizable compounds contained in the composition, from the viewpoint of sufficiently achieving a low dielectric constant and a high Tg of the cured product, and from the viewpoint of reducing the amount of outgassing from the cured product.

[0054] From the viewpoint of suppressing the amount of outgassing from the cured product and increasing the glass transition temperature of the cured product, it is preferable that the composition does not contain a monofunctional oxirane compound (e.g., ethyl glycidyl ether, butyl glycidyl ether, 1,2-epoxyalkane, etc.) formed by bonding a monovalent chain group and an oxiranyl group, or the content of the monofunctional oxirane compound is as low as possible. Specifically, in the composition, the content of the monofunctional oxirane compound formed by bonding a monovalent chain group and an oxiranyl group is preferably 0% by mass or more and 10% by mass or less, more preferably 0% by mass or more and 5% by mass or less, even more preferably 0% by mass or more and 1% by mass or less, and even more preferably 0% by mass or more and 0.5% by mass or less, based on the total amount of the composition.

[0055] The molar ratio of oxiranyl group to oxetanyl group in the polymerizable compound is preferably 1:0.5 to 1:8. By setting the molar ratio of oxiranyl group to oxetanyl group within the above range, the curing reactivity of the present composition can be improved. In addition, the amount of outgas generated from the cured product can be reduced as much as possible, while the dielectric constant of the cured product can be sufficiently reduced. The molar ratio of oxiranyl group to oxetanyl group in the polymerizable compound is more preferably 1:1 to 1:4, and further preferably 1:1 to 1:3.

[0056] <Polymerization initiator> The polymerization initiator may be any material that generates a protonic acid or a Lewis acid in response to heat or light. Such a polymerization initiator may be appropriately selected from known thermal cationic polymerization initiators or photo-cationic polymerization initiators. From the viewpoint of suppressing deterioration of the element, the polymerization initiator is preferably a photo-cationic polymerization initiator. Examples of photo-cationic polymerization initiators include ionic photo-acid generating polymerization initiators or non-ionic photo-acid generating polymerization initiators.

[0057] Examples of the ionic photo-acid generating cationic photopolymerization initiator include onium salt compounds, halogen-containing compounds, sulfone compounds, sulfonic acid compounds, sulfonimide compounds, and diazomethane compounds. Specific examples of the onium salt compounds include compounds in which the cation moiety is an aromatic sulfonium, aromatic iodonium, aromatic diazonium, aromatic ammonium, or (2,4-cyclopentadiene-1-yl)[(1-methylethyl)benzene]-Fe cation and the anion moiety is BF4 - , PF6 - , SbF6 - , [BX4] - (X is a phenyl group substituted with two or more fluorine or trifluoromethyl groups), or [PG6 - ] (wherein G is a fluorinated alkyl group).

[0058] As the polymerization initiator, the onium salt compounds mentioned above are preferably used. Among them, the polymerization initiator is preferably [PF k (C p F 2p+1 ) 6-k ] - It is preferable that the onium fluorinated alkyl fluorophosphate has an anion moiety represented by the formula: [PF k (C p F 2p+1 ) 6-k ] - The anion portion represented by (C p F 2p+1) is 1 or more and has a fluorocarbon chain, so it acts as a relatively strong acid. Therefore, the cationic polymerization performance is high, and it is thought that the use of such onium salts can improve curing properties.

[0059] The cation moiety of the onium fluorinated alkyl fluorophosphate is not particularly limited. Specific examples of the cation moiety include sulfonium cations represented by the following formula (4). [ka] (In formula (4), R 11 ~R 14 are each independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 6 carbon atoms, an alkylcarbonyloxy group having 1 to 6 carbon atoms, an alkylcarbonylthio group having 1 to 6 carbon atoms, or an alkoxycarbonyloxy group having 1 to 6 carbon atoms. r is 0 or 1.)

[0060] In the above formula (4), R 11 ~R 14 is preferably a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a methoxy group, a methylthio group, a methylcarbonyloxy group, a methylcarbonylthio group, or a methoxycarbonyloxy group, and more preferably a hydrogen atom.

[0061] As the ionic photoacid generating cationic photopolymerization initiator, a commercially available product can be used. For example, a cationic moiety represented by the above formula (4) and [PF k (C p F 2p+1 ) 6-k ] - Examples of commercially available products of photocationic polymerization initiators having an anion moiety represented by the formula (I) include "CPI-210S" and "CPI-410S" (both manufactured by San-Apro Co., Ltd.). Examples of commercially available products of aromatic sulfonium salts include "ES-1B" and "ES-1S" (both manufactured by San-Apro Co., Ltd.).

[0062] Examples of non-ionic photoacid generating cationic photopolymerization initiators include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, diazonaphthoquinones, N-hydroxyimidesulfonates, and oxime ester-based carboxylates.

[0063] In the present composition, the content of the polymerization initiator is usually 0.1 to 10 parts by mass relative to 100 parts by mass of the total amount of the polymerizable compounds contained in the present composition. The content of the polymerization initiator is preferably 7 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the total amount of the polymerizable compounds. By setting the content of the polymerization initiator within the above range, the curability of the present composition can be improved, and a cured film with high transparency can be obtained.

[0064] <Other ingredients> In addition to the above-mentioned polymerizable compound and polymerization initiator, the present composition may further contain components other than the polymerizable compound and polymerization initiator (hereinafter, also referred to as "other components"). Examples of the other components include a polymerization inhibitor, an antioxidant, a sensitizer, a surfactant, etc.

[0065] Polymerization inhibitors / antioxidants The composition may further contain at least one compound selected from the group consisting of a polymerization inhibitor and an antioxidant (hereinafter, also referred to as "additive (C)"). By further containing the additive (C), the storage stability of the composition can be improved.

[0066] The polymerization inhibitor is not particularly limited, but examples thereof include hydroquinone, p-methoxyphenol, p-benzoquinone, naphthoquinone, phenanthraquinone, toluquinone, 2,5-diacetoxy-p-benzoquinone, 2,5-dicaproxy-p-benzoquinone, 2,5-acyloxy-p-benzoquinone, 2,5-di-tert-butyl-3-methylphenol, p-tert-butylcatechol, 2,5-di-tert-butylhydroquinone, p-tert-butylcatechol, mono-tert-butylhydroquinone, 2,5-di-tert-amylhydroquinone, di-tert-butyl-paracresolhydroquinone monomethyl ether, phenothiazine, alphanaphthol, acetamidine acetate, acetamidine sulfate, phenylhydrazine hydrochloride, Examples of the suitable amines include hydrazine hydrochloride, trimethylbenzyl ammonium chloride, lauryl pyridinium chloride, cetyl trimethyl ammonium chloride, phenyl trimethyl ammonium chloride, trimethyl benzyl ammonium oxalate, di(trimethyl benzyl ammonium) oxalate, trimethyl benzyl ammonium malate, trimethyl benzyl ammonium tartrate, trimethyl benzyl ammonium glycolate, phenyl-β-naphthylamine, parabenzyl aminophenol, di-β-naphthyl paraphenylenediamine, dinitrobenzene, trinitrotoluene, picric acid, cyclohexanone oxime, pyrogallol, tannic acid, resorcinol, triethylamine hydrochloride, dimethylaniline hydrochloride, and dibutylamine hydrochloride.

[0067] When the additive (C) is blended in the composition, the content of the additive (C) is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, and even more preferably 0.01 to 3 parts by mass, based on 100 parts by mass of the total amount of the polymerizable compounds contained in the composition. By keeping the content within the above range, it is possible to suppress the increase in viscosity due to unnecessary thermal energy and the occurrence of gelation or curing reaction, while maintaining the viscosity of the composition within an appropriate range even after long-term distribution or storage, and to ensure good wetting and spreading properties (and thus inkjet coating properties).

[0068] Antioxidants The antioxidant is used to prevent the curable composition from being deteriorated by oxidation, thereby improving the storage stability of the composition. Examples of the antioxidant include phenol-based antioxidants, sulfur-based antioxidants, and phosphorus-based antioxidants.

[0069] Specific examples of the antioxidant include phenolic antioxidants such as monophenols such as 2,6-di-tert-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-tert-butyl-p-ethylphenol, and stearyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), and 3,9-bis[1,1-dimethyl-2-{β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethane; bisphenols such as 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis-(4'-hydroxy-3'-tert-butylphenyl)butyric acid]glycol ester, 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione, and tocopherol.

[0070] Examples of the sulfur-based antioxidants include dilauryl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, and distearyl-3,3'-thiodipropionate. Examples of phosphorus-based antioxidants include diphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, tris(nonylphenyl) phosphite, diisodecyl pentaerythritol phosphite, tris(2,4-di-tert-butylphenyl) phosphite, cyclic neopentane tetrayl bis(octadecyl) phosphite, cyclic neopentane tetrayl bis(2,4-di-tert-butylphenyl) phosphite, cyclic neopentane tetrayl bis(2,4-di-tert-butyl-6-methylphenyl) phosphite, and and bis[2-tert-butyl-6-methyl-4-{2-(octadecyloxycarbonyl)ethyl}phenyl]hydrogenphosphite; and oxaphosphaphenanthrene oxides such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(3,5-di-tert-butyl-4-hydroxybenzyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-decyloxy-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0071] The antioxidants may be used alone, but are particularly preferably used in combination with phenolic / sulfur or phenolic / phosphorus antioxidants. Also, commercially available phenolic antioxidants (e.g., IRGANOX 1010 (trade name) manufactured by BASF Japan) and commercially available phosphorus antioxidants (e.g., IRGAFOS 168 (trade name) manufactured by BASF Japan) may be used alone or in combination.

[0072] When an antioxidant is blended in the composition, the content of the antioxidant is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, and even more preferably 0.01 to 3 parts by mass, based on 100 parts by mass of the total amount of the polymerizable compounds contained in the composition. By keeping the content within the above range, it is possible to suppress the increase in viscosity due to unnecessary thermal energy and the occurrence of gelation or curing reaction, while maintaining the viscosity of the composition within an appropriate range even after long-term distribution or storage, and to ensure good wetting and spreading properties (and thus inkjet coating properties).

[0073] In addition, in order to improve the storage stability of the composition, in addition to the above-mentioned additive (C), a heat stabilizer such as methylenequinone or 2-dimethylaminomethanol described in JP-A-2020-518952 may be contained in the composition.

[0074] Sensitizer The sensitizer is used for the purpose of minimizing the amount of polymerization initiator used and thereby increasing the transparency of the cured product. Specific examples of the sensitizer include polynuclear aromatics such as pyrene, perylene, triphenylene, anthracene, 9,10-dibutoxyanthracene, 9,10-diethoxyanthracene, 3,7-dimethoxyanthracene, and 9,10-dipropyloxyanthracene; xanthenes such as fluorescein, eosin, erythrosine, rhodamine B, and rose bengal; xanthones such as xanthone, thioxanthone, dimethylthioxanthone, diethylthioxanthone (2,4-diethylthioxanthen-9-one, etc.), and isopropylthioxanthone (2-isopropylthioxanthone, etc.); cyanines such as thiacarbocyanine and oxacarbocyanine; merocyanine, carbomerocyanine, etc. merocyanines; thiazines such as thionine, methylene blue, toluidine blue, etc.; acridines such as acridine orange, chloroflavin, acriflavine, etc.; acridones such as acridone, 10-butyl-2-chloroacridone, etc.; base styryls such as 2-[2-[4-(dimethylamino)phenyl]ethenyl]benzoxazole, etc.; coumarins such as 7-diethylamino-4-methylcoumarin, 7-hydroxy-4-methylcoumarin, 2,3,6,7-tetrahydro-9-methyl-1H,5H,11H[l]benzopyrano[6,7,8-ij]quinolizine-11-one, etc.; rhodacyanines; oxonols; anthraquinones; squaliums; styryls; and the like.

[0075] When a sensitizer is blended in the present composition, the content of the sensitizer is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.2 to 3 parts by mass, relative to 100 parts by mass of the total amount of the polymerizable compounds contained in the present composition. By keeping the content within the above range, the transparency of the cured product can be further improved.

[0076] Surfactants The surfactant can be used to improve the coatability of the composition (specifically, the wetting and spreading properties and the reduction of coating unevenness) and the surface smoothness of the cured product. Examples of the surfactant include fluorine-based surfactants, silicone-based surfactants, and nonionic surfactants.

[0077] Specific examples of surfactants include fluorine-based surfactants, such as MEGAFAC F-171, MEGAFAC F-172, MEGAFAC F-173, MEGAFAC F-251, MEGAFAC F-430, MEGAFAC F-554, MEGAFAC F-556, MEGAFAC F-557, MEGAFAC F-559, MEGAFAC F-560, MEGAFAC F-563 (all manufactured by DIC Corporation); Fluorad FC430, Fluorad FC431 (all manufactured by Sumitomo 3M Limited); Asahi Guard AG710, SA Examples of such additives include Flon S-382, SC-101, SC-102, SC-103, SC-104, SC-105, SC-106, and S-611 (all manufactured by AGC Seimi Chemical Co., Ltd.); Polyflow No. 75 and No. 95 (all manufactured by Kyoeisha Chemical Co., Ltd.); FTX-218 (manufactured by Neos Corporation); F-Top EF301, EF303, and EF352 (all manufactured by Shin-Akita Chemical Co., Ltd.).

[0078] Examples of silicone surfactants include, under the trade names below, SH200-100cs, SH28PA, SH30PA, SH89PA, SH190, SH8400, SH193, SZ6032, SF8428, DC57, DC190, PAINTAD19, FZ-2101, FZ-77, FZ-2118, L-7001, and L-7002 (all manufactured by Dow Corning Toray Co., Ltd.); organosiloxane polymer KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.); and BYK-300, 306, 310, 330, 333, 335, 341, 344, 370, 340, and 345 (all manufactured by BYK Japan).

[0079] Examples of nonionic surfactants include polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene n-octylphenyl ether, polyoxyethylene n-nonylphenyl ether, polyethylene glycol dilaurate, and polyethylene glycol distearate.

[0080] When a surfactant is blended in the present composition, the content of the surfactant is preferably 0.01 to 5 parts by mass, more preferably 0.02 to 3 parts by mass, and even more preferably 0.1 to 2 parts by mass, relative to 100 parts by mass of the total amount of the polymerizable compounds contained in the present composition.

[0081] Examples of other components include, in addition to the above, softeners, plasticizers, adhesion aids, organic solvents, etc. The blending ratio of these components is appropriately selected according to each component within a range that does not impair the effects of the present disclosure.

[0082] An organic solvent may be added to the composition for the purpose of dissolving each component to be added to the composition. On the other hand, from the viewpoint of enabling the formation of a cured film (particularly an organic sealing layer that protects the organic light-emitting layer of an organic EL element) without performing a heat treatment, it is preferable to minimize the amount of organic solvent used. Specifically, the content of the organic solvent in the composition is preferably 0% by mass or more and 3% by mass or less, more preferably 0% by mass or more and 2% by mass or less, even more preferably 0% by mass or more and 1% by mass or less, and even more preferably 0% by mass or more and 0.5% by mass or less.

[0083] When the composition contains an organic solvent, the organic solvent to be used is preferably an organic solvent that can dissolve or disperse each component to be blended in the composition and does not react with each component.Specific examples of the organic solvent include alcohols, ketones, esters, ethers, aromatic hydrocarbons, and amides.

[0084] Specific examples of these include alcohols such as methanol, ethanol, isopropanol, butanol, and octanol. Ketones include acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. Esters include ethyl acetate, butyl acetate, ethyl lactate, γ-butyrolactone, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and methyl-3-methoxypropionate. Ethers include polyoxyethylene lauryl ether, ethylene glycol monomethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, and diethylene glycol methyl ethyl ether. Aromatic hydrocarbons include benzene, toluene, and xylene. Amides include dimethylformamide, dimethylacetamide, and N-methylpyrrolidone.

[0085] The composition of the second embodiment of the present composition (hereinafter also referred to as the "second composition") contains the following compound (A1), compound (A2), and compound (B3) as polymerizable compounds. Compound (A1): A compound represented by the following formula (1): R 1 -X 1 -R 2 …(1) (In formula (1), R 1 and R 2 are each independently a substituted or unsubstituted alicyclic oxiranyl group. 1 is a divalent hydrocarbon group or a halogenated hydrocarbon group. Compound (A2): A polyfunctional polymerizable compound (excluding compound (A1)). Compound (B3): Monofunctional polymerizable compound The second composition will be described below, focusing on the differences from the first composition.

[0086] Specific examples and preferred examples of compound (A1) and compound (A2) contained in the second composition, as well as the contents thereof, are the same as those of the compounds exemplified as compound (A1) and compound (A2) contained in the first composition, and therefore the description thereof will be omitted.

[0087] The compound (B3) contained in the second composition is not particularly limited as long as the dielectric constant of the cured product obtained by curing the second composition at 25°C and a frequency of 250 kHz is 2.70 or less, and the glass transition temperature of the cured product is 85°C or more. In terms of minimizing the generation of outgas from the cured product, a monofunctional polymerizable compound having one oxetanyl group in one molecule (i.e., a monofunctional oxetane compound) can be preferably used as the compound (B3). The proportion of the monofunctional oxetane compound is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 90% by mass or more, based on the total amount of the compound (B3) contained in the second composition.

[0088] The content of the compound (B3) is preferably 30 to 70 mass% based on the total amount of the polymerizable compounds contained in the composition, from the viewpoint of suppressing the viscosity of the curable composition from becoming too high while lowering the dielectric constant of the cured product and improving the wettability and spreadability of the curable composition. From the viewpoint of improving the wettability and spreadability of the curable composition, the content of the compound (B3) is more preferably 35 mass% or more based on the total amount of the polymerizable compounds contained in the composition. In addition, the content of the compound (B3) is more preferably 60 mass% or less, and even more preferably 50 mass% or less based on the total amount of the polymerizable compounds contained in the composition, from the viewpoint of obtaining a cured product having sufficiently high mechanical strength and a low dielectric constant.

[0089] The second composition may contain only the compound (A1), the compound (A2) and the compound (B3) as the polymerizable compound. Alternatively, for the purpose of adjusting the curability or viscosity of the composition, the second composition may further contain a compound different from the compound (A1), the compound (A2) and the compound (B3) in addition to the compound (A1), the compound (A2) and the compound (B3).

[0090] Details of the polymerization initiator contained in the second composition and the components optionally contained in the second composition are the same as those of the first composition, and therefore description thereof will be omitted.

[0091] <Preparation of Curable Composition> The composition can be prepared by mixing a polymerizable compound and a polymerization initiator, as well as other components that are blended as necessary. The content of the polymerizable compound in the composition is preferably 80 parts by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more, based on 100 parts by mass of the total amount of the composition, from the viewpoint of obtaining a curable composition with good sensitivity and forming a cured film with high sealing effect.

[0092] <Viscosity of Curable Composition> The viscosity of the composition measured at 25°C and 20 rpm using an E-type viscometer is preferably in the range of 1.0 to 40.0 mPa·s. When the viscosity of the composition is 40.0 mPa·s or less, the composition has good wetting and spreading properties when applied to a substrate by inkjet coating, and coating unevenness due to repelling or the like can be sufficiently suppressed. When the viscosity of the composition is 1.0 mPa·s or more, the composition can have a sufficient film thickness when applied to a substrate, and an organic sealing layer that fully exhibits a sealing effect can be formed. The composition is suitable as a curable composition for inkjet coating.

[0093] From the viewpoint of obtaining a curable composition having excellent inkjet coatability, the viscosity of the composition is more preferably 35.0 mPa·s or less, even more preferably 30.0 mPa·s or less, and particularly preferably 25.0 mPa·s or less. Moreover, from the viewpoint of stably ejecting the composition by inkjet and ensuring a sufficient film thickness, the viscosity of the composition is more preferably 2.0 mPa·s or more, and even more preferably 5.0 mPa·s or more. In this specification, the viscosity of the curable composition is a value measured in accordance with JIS K2283.

[0094] <Cured product and organic EL element> The cured product of the present disclosure (hereinafter also referred to as the present cured product) is formed from the curable composition prepared as described above. According to the present composition, a cured product having a low dielectric constant, a high glass transition temperature, and less outgassing can be obtained. Such a composition can be used as various materials such as sealing structures for organic EL elements, microlenses, anti-reflection films, and lattices for AR elements. The composition can also be used as a material for forming a hole filling material or a flattening film for holes in HID (Hole In a Display Area) structures and the like. Furthermore, according to the present composition, a cured film having low moisture permeability, which can prevent the intrusion of foreign matter, and excellent bending resistance can be formed, and therefore the composition can also be used as a material for forming a coating layer that protects wiring at the bent portion of a flexible display or at a bent portion where wiring extending from a display unit to the outside is provided. Examples of the coating layer at the bent portion include the micro-coating layer described in International Publication No. 2016 / 09925. The micro-coating layer can be formed by slit coating or inkjet coating. The present composition is useful in that it can be applied to any of these coating methods. The present composition is particularly useful as a composition for forming a sealing structure, that is, a sealant for an organic EL element, which performs thin film encapsulation (TFE) for an organic electroluminescence element (organic EL element) to form a sealing structure.

[0095] <Dielectric constant of the cured product> The present cured product preferably has a dielectric constant of 2.70 or less at 25°C and a frequency of 250kHz. If the dielectric constant under the measurement conditions is 2.70 or less, when a low dielectric constant layer of a device (such as an organic EL light-emitting device) employing a touch panel system is formed from the curable composition, the dielectric constant of the low dielectric constant layer can be sufficiently low, and malfunction during use of the touch panel can be suppressed. From the viewpoint of forming a low dielectric constant layer exhibiting desired performance, the dielectric constant of the cured product at 25°C and a frequency of 250kHz is more preferably 2.69 or less, and even more preferably 2.68 or less. There is no particular limit to the lower limit of the dielectric constant of the cured product. The dielectric constant of the cured product at 25°C and a frequency of 250kHz is, for example, 2.0 or more.

[0096] For details on how to measure the dielectric constant, use a UV-LED lamp with a wavelength of 395 nm and an illuminance of 1,000 mW / cm. 2 And the cumulative light intensity is 1,000mJ / cm 2 The dielectric constant is a value measured at 25°C and a frequency of 250 kHz for a cured product obtained by irradiating the composition with ultraviolet light under the conditions of 1. The details of the method for measuring the dielectric constant are as described in the examples below.

[0097] <Glass transition temperature of the cured product> The present cured product preferably has a glass transition temperature (Tg) of 85°C or higher. When the glass transition temperature of the cured product is 85°C or higher, it is possible to suppress the occurrence of distortion in the lower layer when forming another layer (upper layer) on the layer (lower layer) formed by the curable composition, thereby suppressing the occurrence of cracks. From the viewpoint of suppressing the occurrence of distortion in the cured product formed by the curable composition, the glass transition temperature of the cured product formed by the present composition is more preferably 90°C or higher, even more preferably 95°C or higher, even more preferably 98°C or higher, and even more preferably 100°C or higher. There is no particular limit to the upper limit of the glass transition temperature of the cured product formed by the present composition. The glass transition temperature of the cured product formed by the present composition is, for example, 200°C or lower. The glass transition temperature of the cured product is a value obtained by dynamic viscoelasticity measurement. The details of the method for measuring the glass transition temperature of the cured product are as described in the examples below.

[0098] <Outgassing amount of cured product> When the components of the curable composition (specifically, unreacted polymerizable compounds, solvents, etc.) remain in the cured product formed by the curable composition, outgassing may occur from the cured product due to decomposition products of the unreacted polymerizable compounds, etc. On the other hand, outgassing from the cured product is required to be as small as possible because it may cause deterioration of the element. In this respect, the present composition can provide a cured product with a low outgassing amount. Specifically, when a cured film having a thickness of 8 μm formed by the present composition is heated at 110° C. for 30 minutes, the amount of outgassing from the cured film is preferably 800 ppm or less. The amount of outgassing from the cured film is a value measured by gas chromatography using the headspace method. For details of the method for measuring the amount of outgassing from the cured film, follow the method described in the examples below.

[0099] <<Manufacturing method of organic EL elements>> The present cured product and an organic EL device in which the organic light-emitting layer is encapsulated with the present cured product can be produced using the present composition by a method including the following steps 1 and 2. (Step 1) A step of applying the present composition to the surface of a substrate on which an organic light-emitting layer is formed. (Step 2) A step of forming a sealing structure (organic sealing layer) by curing the composition through irradiation with radiation. Each step will be described in detail below.

[0100] [Process 1: Coating process] In this step, the composition is applied to the light-emitting layer-forming surface of the substrate on which the organic light-emitting layer is formed, thereby forming a coating film made of the composition on the light-emitting layer-forming surface. The substrate to which the composition is applied has a laminate including various layers such as an anode layer, a hole injection layer, a hole transport layer, an electron injection layer, and a cathode layer in addition to the organic light-emitting layer, and this laminate constitutes an organic EL device. The light-emitting layer-forming surface to which the composition is applied may be covered with an inorganic film (inorganic sealing layer). Examples of inorganic materials constituting the inorganic film include silicon nitride (SiNx) and silicon oxide (SiOx). In this case, a thin-film sealing layer including an organic sealing layer and an inorganic sealing layer is formed as a sealing structure on the organic light-emitting layer.

[0101] Examples of methods for applying the composition include spraying, roll coating, spin coating, slit die coating, bar coating, and inkjet coating. Among these, inkjet coating is preferably used from the viewpoints of throughput and thinning. The composition has low viscosity but exhibits excellent curability, and the occurrence of coating unevenness is suppressed, so that it can be suitably used for inkjet coating.

[0102] [Process 2: Curing process] In this step, the coating film formed in step 1 above is irradiated with radiation to cure the coating film, thereby obtaining a cured film. Examples of radiation include ultraviolet light, far ultraviolet light, visible light, X-rays, and charged particle beams such as electron beams. Among these, ultraviolet light is preferred, and for example, ultraviolet light having a wavelength of 350 to 400 nm can be preferably used as the irradiation light. The radiation exposure amount is 0.05 to 10 J / m 2This makes it possible to obtain an organic EL device covered with an organic sealing layer made of the present composition. The thickness of the cured film is usually 0.5 to 15 μm.

[0103] The organic sealing layer formed by the present composition may be further covered with an inorganic film (inorganic sealing layer). Examples of inorganic materials constituting the inorganic film include silicon nitride (SiNx) and silicon oxide (SiOx). When a thin-film sealing layer including an organic sealing layer and an inorganic sealing layer is provided on an organic EL device, the organic sealing layer can be appropriately hardened by forming the organic sealing layer by the present composition. This makes it possible to suppress the occurrence of cracks in the organic sealing layer even when an inorganic sealing layer is further formed on the surface of the organic sealing layer.

[0104] The organic EL element of the present disclosure manufactured by the method including the above-mentioned steps 1 and 2 includes an organic light-emitting layer and an organic sealing layer made of the present composition, and the organic light-emitting layer is sealed by the organic sealing layer. Therefore, in the organic EL element of the present disclosure, the intrusion of moisture into the organic light-emitting layer can be sufficiently suppressed, and thus the inconvenience caused by moisture, specifically the occurrence of dark spots and the decrease in light-emitting properties such as brightness and light-emitting efficiency, can be suppressed. In addition, in the organic EL element of the present disclosure, the generation of outgas from the organic sealing layer is small, and the dielectric constant of the organic sealing layer is sufficiently low. Such an organic EL element of the present disclosure is useful, for example, as an organic EL lighting device or an organic EL display device.

[0105] According to the present disclosure described above in detail, the following means are provided. [Means 1] A curable composition containing a polymerizable compound and a polymerization initiator, the polymerizable compound including a compound (A1) represented by the above formula (1), a compound (A2) which is a polyfunctional polymerizable compound (excluding the compound (A1)), and a compound (A3) which is a monofunctional polymerizable compound having one oxetanyl group in one molecule, the total amount of the compound (A1), the compound (A2) and the compound (A3) being 85 mass% or more based on the total amount of the polymerizable compounds. [Means 2] The curable composition according to [Means 1], comprising 10 to 60 mass% of the compound (A1), 5 to 70 mass% of the compound (A2), and 20 to 70 mass% of the compound (A3) relative to the total amount of the polymerizable compounds. [Means 3] The curable composition according to [Means 1] or [Means 1], wherein a molar ratio of oxiranyl groups to oxetanyl groups in the polymerizable compound is 1:0.5 to 1:8. [Measure 4] The curable composition according to any one of [Measure 1] to [Measure 3], wherein the proportion of the polyfunctional oxetane compound in the compound (A2) is 30 mass % or more. [Means 5] The curable composition according to any one of [Means 1] to [Means 4], wherein the compound (A1) is represented by the above formula (1-1). [Means 6] R in the above formula (1-1) 3 and R 4 The curable composition according to [means 5], wherein is a methyl group. [Means 7] The curable composition according to any one of [Means 1] to [Means 6], wherein the content of the monofunctional oxirane compound formed by bonding a monovalent chain group and an oxiranyl group is 10 mass % or less of the entire composition. [Means 8] The curable composition according to any one of [Means 1] to [Means 7], wherein a cured product of the curable composition has a dielectric constant of 2.70 or less at 25° C. and a frequency of 250 kHz. [Means 9] The curable composition according to any one of [Means 1] to [Means 8], wherein a glass transition temperature of a cured product of the curable composition is 85° C. or higher. [Means 10] The curable composition according to any one of [Means 1] to [Means 9], which is for inkjet coating. [Measures 11] The curable composition according to any one of [Measures 1] to [Measures 10], which is used for forming a sealing structure for sealing an organic light-emitting layer of an organic EL element. [Means 12] A curable composition containing a polymerizable compound and a polymerization initiator, the polymerizable compound including a compound represented by the above formula (1), a compound which is a polyfunctional polymerizable compound (excluding the above compound (A)), and a compound which is a monofunctional polymerizable compound, the curable composition having a dielectric constant of 2.70 or less at 25°C and at a frequency of 250 kHz and a glass transition temperature of 85°C or more. [Means 13] A cured film formed using the curable composition according to any one of [Means 1] to [Means 12]. [Means 14] An organic EL element comprising an organic light-emitting layer and an organic sealing layer that seals the organic light-emitting layer, the organic sealing layer being formed using the curable composition according to any one of [Means 1] to [Means 12]. [Means 15] A method for producing an organic EL element comprising an organic light-emitting layer and an organic sealing layer sealing the organic light-emitting layer, the method comprising the steps of: applying a curable composition according to any one of [Means 1] to [Means 12] to a light-emitting layer-forming surface of a substrate on which the organic light-emitting layer is formed; and forming the organic sealing layer by irradiating radiation to cure the curable composition. [Means 16] The method for producing an organic EL element according to [Means 15], wherein the curable composition is applied by inkjet coating. EXAMPLES

[0106] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.

[0107] 1. Preparation of Curable Composition The components used in preparing the curable compositions were as follows: <Polymerizable compound> ·Multifunctional compounds A1-1: A compound described in formula (5)

[0106] of Korean Patent Publication No. 10-2022-0160362 A2-1: OXT-221 (3,3'-(oxybismethylene)bis(3-ethyloxetane, manufactured by Toagosei Co., Ltd.) A2-2: Celloxide 2021P (manufactured by Daicel Corporation) A2-3: Celloxide 8010 (manufactured by Daicel Corporation) A2-4: KR-470 (Shin-Etsu Chemical Co., Ltd.) A2-5: X-40-2669 (Shin-Etsu Chemical Co., Ltd.) A2-6: X-40-2678 (Shin-Etsu Chemical Co., Ltd.) ·Monofunctional compounds A3-1: OXT-212 (3-ethyl-3-[(2-ethylhexyloxy)methyl]oxetane, manufactured by Toagosei Co., Ltd.) A3-2: 1,2-epoxytetradecane (manufactured by Yokkaichi Chemical Co., Ltd.) <Polymerization initiator> B-1: Photocationic polymerization initiator (SAN-APRO "CPI-210S") Sensitizer C-1: 9,10-dibutoxyanthracene <Surfactants> D-1: Silicone-containing nonionic surfactant (BYK-333, manufactured by BYK Japan)

[0108] [Example 1] Under atmospheric conditions, 50 parts by mass of compound (A1-1), 10 parts by mass of compound (A2-1), 40 parts by mass of compound (A3-1), 3 parts by mass of polymerization initiator (B-1), 1 part by mass of sensitizer (C-1), and 1 part by mass of surfactant (D-1) were mixed to prepare a curable composition.

[0109] [Examples 2 to 6 and Comparative Examples 1 to 6] Curable compositions were prepared in the same manner as in Example 1, except that the types and amounts of the polymerizable compounds were changed as shown in Table 1. In Table 1, the numerical value in the column "Oxetanyl group / oxiranyl group [mol / mol]" indicates the molar ratio of oxiranyl group to oxetanyl group in the polymerizable compound used for preparing each curable composition. The molar ratio was determined from the blending composition of the polymerizable compound.

[0110] 2. Evaluation The curable compositions of Examples 1 to 6 and Comparative Examples 1 to 6 were evaluated for the following items by the methods described below. The evaluation results are shown in Table 1.

[0111] <Dielectric constant of cured film> The curable composition was applied to a substrate, on which ITO had been deposited to a thickness of 30 nm on non-alkali glass, using a spin coater so that the cured thickness would be 8 μm. Next, an LED UV lamp was used to irradiate the composition with ultraviolet light of 395 nm at an illuminance of 1000 mW / cm. 2 , cumulative light intensity 1,000mJ / cm 2 The curable composition was cured by irradiation to form a cured film. As the LED UV lamp, UniJet E110Z HD (Type U395A-455, manufactured by Ushio Inc.) was used. Then, aluminum was evaporated to a thickness of 50 nm on the surface of the cured film to prepare a test piece for dielectric constant measurement. The dielectric constant of the obtained test piece was measured at 25°C and 250 kHz using a dielectric constant measuring device. As the dielectric constant measuring device, a 4284A LCR meter (manufactured by Hewlett Packard Co.) was used.

[0112] <Glass transition temperature (Tg) of cured film> The curable composition was applied by spin coating to a 95 mm square glass substrate that had been subjected to a release treatment. The curable composition was then cured by irradiating it with 395 nm ultraviolet light under nitrogen using an LED lamp to form a cured film. The cured film formed on the glass substrate was peeled off from the substrate to obtain a cured film with a thickness of 60 μm. The glass transition temperature of the cured film was measured by measuring the peak top of Tan δ using a dynamic viscoelasticity measuring device ("DVA-225" manufactured by IT Measurement and Control Co., Ltd.).

[0113] <Outgassing amount> The amount of gas (outgas) generated when a cured film of the curable composition was heated was measured by gas chromatography using the headspace method. The measurement was performed as follows. First, the curable composition was applied to a thickness of 8 μm using a spin coater. Next, an LED lamp was used to apply ultraviolet light with a wavelength of 395 nm at an illuminance of 1,000 mW / cm. 2 , cumulative light intensity 1,000mJ / cm 2 After curing under the conditions above, the cured film was placed in a headspace vial, the vial was sealed, and heated at 110° C. for 30 minutes, and the amount of outgassing was measured by the headspace method. ○: Outgassing amount is 300 ppm or more and less than 800 ppm ×: Outgassing amount is 800 ppm or more

[0114] [Table 1]

[0115] As shown in Table 1, the cured films formed from the curable compositions of Examples 1 to 6 had a high glass transition temperature of 85° C. or more, a low dielectric constant of less than 2.70, and a small amount of outgassing. Among these, the cured film formed from the curable composition containing 20% ​​by mass or more of the compound (A1-1) based on the total amount of the polymerizable compounds had a high glass transition temperature of 100° C. or more, but a low dielectric constant of less than 2.65, and the cured film was able to have a high Tg and a low dielectric constant (Examples 1 to 4). In addition, the cured film formed from the curable composition containing 70% by mass or more of the total amount of the compound (A1) and the compound (A2) based on the total amount of the polymerizable compounds also had a high glass transition temperature of 100° C. or more, but a low dielectric constant of 2.65, and the cured film was able to have a high Tg and a low dielectric constant (Example 6).

[0116] In contrast, the cured films formed from the curable compositions of Comparative Examples 1 and 2 had sufficiently high glass transition temperatures, but a dielectric constant higher than 2.70. The cured film formed from the curable composition of Comparative Example 3 had a low glass transition temperature of 55°C, and a high dielectric constant of 2.72. The cured films formed from the curable compositions of Comparative Examples 4 to 6 had dielectric constants lower than 2.70, but a glass transition temperature lower than 80°C. The cured film of Comparative Example 6 also had a large amount of outgassing.

Claims

1. A curable composition for forming a sealing structure that seals an organic light-emitting layer of an organic EL element, comprising: a polymerizable compound and a polymerization initiator, The polymerizable compound is The following formula (1): R 1 -X 1 -R 2 …(1) (In formula (1), R 1 and R 2 are each independently a substituted or unsubstituted alicyclic oxiranyl group. 1 is represented by the following formula (1b): *-C(R 3 )(R 4 )-*...(1b) (In formula (1b), R 3 and R 4 are each independently a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a fluoroalkyl group having 1 to 3 carbon atoms, or a phenyl group, or R 3 and R 4 taken together represent an alicyclic structure formed together with the carbon atom to which R 3 and R 4 are bonded. "*" represents a bond to the alicyclic oxirane ring structure.) It is a divalent group represented by the following formula: A compound (A1) represented by the formula: A compound (A2) which is a polyfunctional polymerizable compound (excluding the compound (A1)), A compound (A3) which is a monofunctional polymerizable compound having one oxetanyl group in one molecule; Including, the compound (A2) is a polyfunctional oxetane compound, or a polyfunctional oxetane compound and a polyfunctional alicyclic oxirane compound; the total amount of the compound (A1), the compound (A2), and the compound (A3) is 85 mass% or more based on the total amount of the polymerizable compounds, A curable composition for forming a sealed structure, comprising a monofunctional oxirane compound in which a monovalent chain group and an oxiranyl group are bonded to each other, the monofunctional oxirane compound being 10 mass % or less of the total composition.

2. 2. The curable composition for forming a sealing structure according to claim 1, comprising 10 to 60 mass% of the compound (A1), 5 to 70 mass% of the compound (A2), and 20 to 70 mass% of the compound (A3) relative to a total amount of the polymerizable compounds.

3. 2. The curable composition for forming a sealing structure according to claim 1, wherein a molar ratio of oxiranyl groups to oxetanyl groups in the polymerizable compound is from 1:0.5 to 1:

8.

4. The curable composition for forming a sealing structure according to claim 1 , wherein the proportion of the polyfunctional oxetane compound in the compound (A2) is 30 mass % or more.

5. The curable composition for forming a sealing structure according to claim 1, wherein the compound (A1) is represented by the following formula (1-1): 【Chemistry 1】 (In formula (1-1), R 3 and R 4 are each independently a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a fluoroalkyl group having 1 to 3 carbon atoms, or a phenyl group, or R 3 and R 4 are combined together and R 3 and R 4 represents an alicyclic structure formed together with the carbon atom to which R is bonded. 5 and R 6 are each independently an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 20 carbon atoms. n1 and n2 are each independently an integer of 0 to 3.

6. R in the above formula (1-1) 3 and R 4 The curable composition for forming a sealing structure according to claim 5 , wherein is a methyl group.

7. 2. The curable composition for forming a sealing structure according to claim 1, wherein a cured product of the curable composition has a dielectric constant of 2.70 or less at 25° C. and a frequency of 250 kHz.

8. The curable composition for forming a sealing structure according to claim 1 , wherein a glass transition temperature of a cured product of the curable composition is 85° C. or higher.

9. The curable composition for forming a sealing structure according to claim 1 , which is for inkjet coating.

10. A curable composition for forming a sealing structure that seals an organic light-emitting layer of an organic EL element, comprising: a polymerizable compound and a polymerization initiator, The polymerizable compound is The following formula (1): R 1 -X 1 -R 2 …(1) (In formula (1), R 1 and R 2 are each independently a substituted or unsubstituted alicyclic oxiranyl group. 1 is represented by the following formula (1b): *-C(R 3 )(R 4 )-* …(1b) (In formula (1b), R 3 and R 4 are each independently a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a fluoroalkyl group having 1 to 3 carbon atoms, or a phenyl group, or R 3 and R 4 are combined together and R 3 and R 4 represents an alicyclic structure formed together with the carbon atom to which it is bonded. "*" represents a bond to the alicyclic oxirane ring structure.) It is a divalent group represented by the following formula: A compound (A1) represented by the formula: A polyfunctional polymerizable compound (excluding the compound (A1)), A monofunctional polymerizable compound, Including, the polyfunctional polymerizable compound is a polyfunctional oxetane compound, or a polyfunctional oxetane compound and a polyfunctional alicyclic oxirane compound; the monofunctional polymerizable compound is a monofunctional oxetane compound, the content of a monofunctional oxirane compound formed by bonding a monovalent chain group and an oxiranyl group is 10 mass% or less of the entire composition, the cured product of the curable composition for forming a sealing structure has a dielectric constant of 2.70 or less at 25° C. and a frequency of 250 kHz; The curable composition for forming a sealing structure, wherein the glass transition temperature of the cured product is 85° C. or higher.

11. A cured film formed using the curable composition for forming a sealing structure according to any one of claims 1 to 10.

12. An organic light-emitting layer; an organic sealing layer that seals the organic light-emitting layer; Equipped with An organic EL element, wherein the organic sealing layer is formed using the curable composition for forming a sealing structure according to any one of claims 1 to 10.

13. A method for manufacturing an organic EL element including an organic light-emitting layer and an organic sealing layer that seals the organic light-emitting layer, comprising the steps of: A step of applying the curable composition for forming a sealing structure according to any one of claims 1 to 10 to a light-emitting layer-forming surface of the substrate on which the organic light-emitting layer is formed; forming the organic sealing layer by curing the curable composition for forming a sealing structure by irradiating radiation; A method for producing an organic EL element comprising the steps of:

14. The method for producing an organic EL element according to claim 13 , wherein the curable composition for forming a sealing structure is applied by inkjet coating.

Citation Information

Patent Citations

  • Cationic curing composition for metal substrate, coating, metal product and application

    CN112574650A

  • Dental curable composition

    JP2012116808A

  • Photocurable composition, and cured product and optical component using same

    JP2018141028A

  • Curable composition and compound

    JP2020026515A

  • Cationic curing compositions for plastic substrates, coatings, plastic products and uses

    JP2022550399A